Analysis of Sanitation Fulfillment with Visitors Comfort in Kreo Cave Semarang - Yuantari, Maria Goretti Catur; Aryaningrum, Novia; Ariyanto, Amelia Devi Putri (Journal of Health Education, 2022)
Background: Enjoying natural beauty, fresh air, and beautiful scenery has become a necessity at this time. Identification of sanitation compliance and visitors' comfort level at tourist sites needs to be done to increase visitor comfort, which can increase tourist attraction. This study aimed to analyze the relationship between the fulfillment of sanitation to the comfort level of visitors to tourist attractions. Methods: The research method used is cross-sectional, with the number of respondents as many as 100 people. The research location is in the tourist area of Kreo Cave, Semarang. Results: The results showed that there was a relationship between the fulfillment of sanitation and the comfort level of visitors to Kreo Cave (P-value <0.005) with a reasonably strong relationship strength (Rho: 0.370). Conclusions: The better the fulfillment of sanitation, the more perceived level of comfort by visitors. Fulfillment of toilet cleanliness, availability of water, friendliness of officers, and implementation of health protocols makes visitors feel comfortable at tourist attractions. However, in this tourist spot, it is necessary to install a disaster evacuation route signboard that has not been carried out by the tourist spot manager and improve the cleanliness of the food and beverage sellers. KEYWORDS: Sanitation; Comfort Level; Visitors; Tourist Attractions; Kreo Cave